Bidirectional causality of physical exercise in retinal neuroprotection - Stephen K. Agadagba; Suk-yu Yau; Ying Liang; Kristine Dalton; Benjamin Thompson (Neural Regeneration Research)
Physical exercise is recognized as an effective intervention to improve mood, physical performance, and general well-being. It achieves these benefits through cellular and molecular mechanisms that promote the release of neuroprotective factors. Interestingly, reduced levels of physical exercise have been implicated in several central nervous system diseases, including ocular disorders. Emerging evidence has suggested that physical exercise levels are significantly lower in individuals with ocular diseases such as glaucoma, age-related macular degeneration, retinitis pigmentosa, and diabetic retinopathy. Physical exercise may have a neuroprotective effect on the retina. Therefore, the association between reduced physical exercise and ocular diseases may involve a bidirectional causal relationship whereby visual impairment leads to reduced physical exercise and decreased exercise exacerbates the development of ocular disease. In this review, we summarize the evidence linking physical exercise to eye disease and identify potential mediators of physical exercise-induced retinal neuroprotection. Finally, we discuss future directions for preclinical and clinical research in exercise and eye health.